Locating poor livestock keepers at the global level for research and development targeting - Thornton, Philip K.; Kruska, Russell L.; Henninger, N.; Kristjanson, Patricia M.; Reid, Robin S.; Robinson, Timothy P. (Elsevier, 2003)
Many research and development agencies are committed to halving the number of people living in extreme poverty by 2015. Knowledge of where the poor are, and what characterises them, is patchy at best. Here we describe a global livestock and poverty mapping study designed to assist in targeting research and development activities concerning livestock. Estimates of the numbers of poor livestock keepers by production system and region are presented. While these estimates suffer from various problems, improvements in global databases are critical to improve the targeting of interventions that can meet the challenges posed by poverty and to chart progress against international development indicators.